Prayer in the Bose monastic community - Dotti, Guido (2024)
A monastic community comprising brothers and sisters of different Christian denominations has, since its beginnings, needed to create a structure for daily common prayer, in which community members and guests could feel welcomed. At Bose we tried to place the Word of God at the heart of prayer, through the singing of psalms with antiphons taken from the Bible and the proclamation of the entire New Testament in one year and the Old Testament in three years. The composition of the prayers of praise, contemplation, and intercession is nourished by the liturgical heritage of the different Christian denominations and by reference to biblical texts, trying to use language which is comprehensible today. During the Eucharistic celebration, the wound of the division between the Churches remains open, but it also becomes an invocation for a full visible unity of Christians.
Keywords: Christian Prayers & Devotions; Old Testament; Word Of God In Christianity